Epidemiological profile of deaths from breast cancer and covid-19 (Research, Society and Development, 2021)
Cancer patients are at higher risk for the development of COVID-19 disease in its most severe form. Objective: to analyze mortality from breast cancer associated with COVID-19 in Brazilian women. Methodology: This is a quantitative study. Data were collected on the Open Data SUS website, from January to August 2020. Descriptive statistics were used for data analysis. Results: breast cancer associated with COVID-19 caused 69 deaths in this period, the ages with the highest number of deaths were in the age ranges 45-49 (14.5%), 60-64 (14.5%) and 65-69 years (14.5%). Regarding race, (56.52%) were white, followed by brown (31.88%). Only (31.88%) had 8 years or more of education and (49.27%) were married. Regarding the underlying cause of death, he presented ICD B34.2 (Infection by Coronavirus of unspecified location) in greater numbers, with a frequency of 52 (75.36%) and ICD C50.9 (Malignant breast cancer, unspecified) had a frequency of 17 (24.64%). The city with the highest number of deaths from breast cancer associated with COVID-19, which reached 14 (20.29%) of cases, was Rio de Janeiro (RJ), followed by the city of São Bernardo do Campo (SP) with 5 (7.25 %). Conclusion: The increase in breast cancer mortality during the COVID-19 pandemic in Brazil can be attributed to the immunosuppression of these women and the COVID-19 coping measures, which reduced the demand for health care, access and availability of diagnostic services.